Patterns of empire : the British and American empires, 1688 to the present - Go, Julian, 1970- (New York : Cambridge University Press, 2011)
"Patterns of empire comprehensively examines the two most powerful empires in modern history: the United States and Britain. Challenging the popular theory that the American empire is unique, Patterns of empire shows how the policies, practices, forms, and historical dynamics of the American empire repeat those of the British, leading up to the present climate of economic decline, treacherous intervention in the Middle East, and overextended imperial confidence. A critical exercise in revisionist history and comparative social science, this book also offers a challenging theory of empire that recognizes the agency of non-Western peoples, the impact of global fields, and the limits of power"--
Introduction -- Imperial paths to power -- Colonial rules -- Hegemonies and empires -- Imperial forms, global fields -- Weary Titans : declining powers, new imperialisms -- The dynamics of imperialism -- Conclusion.
Includes bibliographical references (pages 251-281) and index.
Keywords: United States -- Foreign relations; Great Britain -- Foreign relations; Imperialism -- History; United States -- Territorial expansion; Great Britain -- Territorial expansion; United States -- Foreign relations; Great Britain -- Foreign relations; United States -- Territorial expansion; Great Britain -- Territorial expansion; HISTORY -- Renaissance; Imperialism; Diplomatic relations; Territorial expansion; Great Britain; United States; Imperialismus; Hegemonie; USA; Imperialismus; Hegemonie; USA; History